Renewable energy using solid state fuel cell technology - Lui, Su Chang (2015)
In today’s world, energy has played an important part in our lives. With technological advancement, our consumption of energy is ever increasing. In order to sustain energy for use in our lifetime, we have to rely on renewable energy that will not emit any pollutants. One of the renewable energy that has zero emission is the use of fuel cell technology. The aim of this study is to investigate the applications of fuel cell technology as renewable energy. The fuel cell technology produces electricity by combining hydrogen with oxygen using an electrochemical process. The by-products are just water and heat. However, there are shortcomings of using fuel cell technology depending on the types of fuel cell used in the application. In this study, the development of the fuel cell technology in terms of its history and types of fuel cell will be introduced. Then, the methods of harvesting the fuel will be analysed. Next, the progress of fuel cell technology in different types of applications will be examined. Finally, concluding by recommending possible future development and give a summary.